Honey ameliorate negative effects in neurodegenerative diseases: an evidence-based review - Abid Nordin; Ruszymah Hj Idrus; Aminuddin Saim (Penerbit Universiti Kebangsaan Malaysia, 2021)
Neurodegenerative diseases are cluster of disorders arising from neuronal cell death in the central nervous system. Its prevalence increases with increasing age. Therapeutic options for neurodegenerative disease include protection against oxidative damage, attenuation of neuroinflammation, maintenance of essential neurotransmitters, and protection against environmental factors that induce neurotoxicity. Honey with its antioxidative, anti-inflammatory, and cytoprotective effects is a potential candidate for therapy in neurodegenerative diseases. The present evidence-based review summarizes the effects of honey on neurodegenerative diseases in non-human subjects. Three electronic databases, namely PubMed, Ovid Medline and Scopus were searched for records published from inception of database to May 2020 to identify reports on the association of honey and neurodegenerative diseases. Based on the preset eligibility criteria, 8 qualified articles were selected and discussed in this review. Honey from different geological origin around the globe was used by different researcher among the studies included. Honey confers protection against oxidative stress induced by hypoxia and metabolic syndrome, aluminium toxicity, and neuroinflammation. Honey also demonstrated potential ability to inhibit neurotransmitters degrading enzymes and restore memory impairment. This review showed a sparse body of evidence on the potential of honey as neurodegenerative disease therapy.